Prediction of Shrinkage Porosity in Femoral Stem of Titanium Investment Casting - Sutiyoko; Suyitno; Mahardika Muslim; Syamsudin A. (Archives of Foundry Engineering, 2016)
Design of gating system is an important factor in obtaining defect-free casting. One of the casting defects is a porosity caused by internal shrinkage in solidification process. Prediction of the internal shrinkage porosity in the femoral stem of commercially pure titanium (CP-Ti) is investigated based on the gating system design. The objective of this research is to get the best gating system between three gating system designs. Three gating system designs of the femoral stem were simulated in an investment casting method. The internal shrinkage porosity occurs on the largest part and near the ingate of the femoral stem. The gating system design that has ingates cross section area: 78.5; 157; and 128.5 mm2 has the least of the internal shrinkage porosity. This design has the most uniform solidification in the entire of the femoral stem. An experiment is conducted to validate the simulation data. The results of internal shrinkage porosity in the three gating system designs in the simulation were compared with the experiment. Based on the comparison, the trend of internal shrinkage porosity at the three gating system designs in the simulation agrees with the experiment. The results of this study will aid in the elimination of casting defect.